Improved Cardiac Function in Infarcted Mice after Treatment with Pluripotent Embryonic Stem Cells - Nelson, Timothy J. (2006)
Because pluripotent embryonic stem cells (ESCs) are able to differentiate into any tissue, they are attractive agents for tissue regeneration. Although improvement of cardiac function has been observed after transplantation of pluripotent ESCs, the extent to which these effects reflect ESC-mediated re-muscularization, re-vascularization or paracrine mechanisms is unknown. Moreover, because ESCs may generate teratomas, the ability to predict the outcome of cellular differentiation, especially when transplanting pluripotent ESCs, is essential; conversely, a requirement to use pre-differentiated ESCs would limit their application to highly characterized subsets that are available in limited numbers. In the experiments reported here we transplanted low numbers of two murine ESC lines, respectively engineered to express a β-galactosidase gene from either a constitutive (elongation factor, EF) or a cardiac-specific (α-myosin heavy chain, α-MHC) promoter, into infarcted mouse myocardium. Although ESC-derived tumors formed within the pericardial space in 21% of injected hearts, lacZ histochemistry revealed that engraftment of ESC was restricted to the ischemic myocardium. Echocardiographic monitoring of ESC-injected hearts that did not form tumors revealed functional improvements by four weeks post-infarction, including significant increases in ejection fraction (EF), circumferential fiber shortening velocity (VCF) and peak mitral bloodflow velocity (peak-E). These experiments indicate that the infarcted myocardial environment can support engraftment and cardiomyogenic differentiation of pluripotent ESCs, concomitant with partial functional recovery.